The Effects of Monetary Policies on the Capital Structures of the Firms - Octávio Valente Campos; Wagner Moura Lamounier (BBR: Brazilian Business Review)
The purpose of this paper is to analyze the influence that monetary policies have on the financing decisions of Brazilian corporations. From this purpose, two hypotheses will be derived. The study sample is composed of 220 companies: 84 of consumer goods, 89 of capital assets, and 47 of public utility. The data collected refer to the years from 2009 to 2019, and the methodology used for data analysis is through quantile regressions and panel data models, using the GMM approach. According to the results, it can be concluded-in the light of the market timing theory, in line with the Austrian theory of economic cycles-that the capital structures of firms can be determined by the market moments, as defined by monetary policies, so that such influence is different depending on the sector to which the companies are located in the production chain.